A new taxonomy for postactivation potentiation in sport - Boullosa, Daniel; Beato, Marco; Iacono, Antonio Dello; Cuenca-Fernández, Francisco; Doma, Kenji; Schumann, Moritz; Zagatto, Alessandro Moura [UNESP]; Loturco, Irineu; Behm, David G. (Human Kinetics, 2020)
Postactivation potentiation (PAP) mechanisms and responses have a long scientific history. However, to this day there is still controversy regarding the mechanisms underlying enhanced performance after a conditioning activity. More recently, the term postactivation performance enhancement (PAPE) has been proposed with differing associated mechanisms and protocols than with PAP. However, these 2 terms (PAP and PAPE) may not adequately describe all specific potentiation responses and mechanisms and can also be complementary, in some cases. Purpose: This commentary presents and discusses the similarities and differences between PAP and PAPE and, subsequently, elaborates on a new taxonomy for better describing performance potentiation in sport settings. Conclusion: The elaborated taxonomy proposes the formula “Post-[CONDITIONING ACTIVITY] [VERIFICATION TEST] potentiation in [POPULATION].” This taxonomy would avoid erroneous identification of isolated physiological attributes and provide individualization and better applicability of conditioning protocols in sport settings.
Keywords: Athletic performance; Power; Priming exercise; Strength; Warm-up